Socioeconomic inequalities in parent-reported and teacher-reported psychological well-being. Issue 1 (27th August 2014) - Lewis, Hannah; Hope, Steven; Pearce, Anna
Abstract : Objective: To determine whether there are differences in the social gradient of parent-reported and teacher-reported child psychological well-being. Design: Secondary data analysis comparing ratings of child psychological well-being (Strengths and Difficulties Questionnaire, SDQ) in the UK Millennium Cohort Study at 7 years by socioeconomic circumstances (SEC). A number of measures of SEC were tested; results are reported for maternal education. From a sample of 13 168 singletons who participated at the age of 7 years, complete data were available for 8207 children. Results: There was a social gradient in SDQ scores reported by parents and teachers, with 'borderline/abnormal' scores more prevalent in children with lower-educated mothers. However, the gradient was more marked in parent report compared with teacher report, and discrepancies between parent and teacher reports were greatest for children from higher SECs. Conclusions: The social gradient in child psychological well-being, although present, was weaker in teacher report compared with parent report. This may be because children behave differently in school and home settings, or parents and teachers demonstrate reporting bias.